Pemberdayaan Subak Penarungan sebagai Lembaga Agribisnis di Desa Penarungan, Kecamatan Mengwi, Kabupaten Badung - NYOMAN EDY DARMAYASA; NYOMAN PARINING; WAYAN SUDARTA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Empowerment of Subak Penarungan as an Agribusiness Institution in PenarunganVillage, Sub-District of Mengwi, Badung Regency The preservation of subak or Balinese irrigation organization is important because itssustainability in Bali based on the Tri Hita Karana concepts. Subak-based economicbusiness is a food-based agribusiness or paddy fields. The studies on empowerment ofsubak as an agribusiness institution aimed to improve the economy and welfare offarmers, so that the agricultural culture is in demand and not abandoned by the SubakPenarungan community. This study aimed to determine (1) the potentials of subakrelated to natural resources, human resources, and financial resources, (2) the effortsmade to empower Subak Penarungan as an agribusiness institution. The research wasconducted in Subak Penarungan, Mengwi Sub-district, Badung Regency. The selectionof research site was done purposively. The population of this study is active members ofSubak Penarungan, amounting to 167 people. The sample size was determined by usingSlovin formula, so the number of respondents was 63 people. The data analysis used adescriptive qualitative analysis method. The findings showed that the potential of Subakpenarungan was in good category with the average score of 3.55, and the results ofresearch on the efforts of empowerment of Subak Penarungan was in good category,with average achievement score of 3.50. Based on the results of this study, it can besuggested to farmers that the assistance in the form of agricultural machine toolsprovided by the government for subak should be utilized properly, so as to increase theirproductivity.